Index: The Book of Statistical ProofsStatistical Models ▷ Univariate normal data ▷ Analysis of variance ▷ Ordinary least squares for two-way ANOVA

Theorem: Given the two-way analysis of variance assumption

$\label{eq:anova2} \begin{split} y_{ijk} &= \mu + \alpha_i + \beta_j + \gamma_{ij} + \varepsilon_{ijk} \\ \varepsilon_{ijk} &\overset{\mathrm{i.i.d.}}{\sim} \mathcal{N}(0, \sigma^2), \; i = 1, \ldots, a, \; j = 1, \ldots, b, \; k = 1, \dots, n_{ij} \; , \end{split}$

the parameters minimizing the residual sum of squares and satisfying the constraints for the model parameters are given by

$\label{eq:anova2-ols} \begin{split} \hat{\mu} &= \bar{y}_{\bullet \bullet \bullet} \\ \hat{\alpha}_i &= \bar{y}_{i \bullet \bullet} - \bar{y}_{\bullet \bullet \bullet} \\ \hat{\beta}_j &= \bar{y}_{\bullet j \bullet} - \bar{y}_{\bullet \bullet \bullet} \\ \hat{\gamma}_{ij} &= \bar{y}_{i j \bullet} - \bar{y}_{i \bullet \bullet} - \bar{y}_{\bullet j \bullet} + \bar{y}_{\bullet \bullet \bullet} \end{split}$

where $\bar{y} _{\bullet \bullet \bullet}$, $\bar{y} _{i \bullet \bullet}$, $\bar{y} _{\bullet j \bullet}$ and $\bar{y} _{i j \bullet}$ are the following sample means:

$\label{eq:mean-samp} \begin{split} \bar{y}_{\bullet \bullet \bullet} &= \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \bar{y}_{i \bullet \bullet} &= \frac{1}{n_{i \bullet}} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \bar{y}_{\bullet j \bullet} &= \frac{1}{n_{\bullet j}} \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \bar{y}_{i j \bullet} &= \frac{1}{n_{ij}} \sum_{k=1}^{n_{ij}} y_{ijk} \end{split}$

with the sample size numbers

$\label{eq:samp-size} \begin{split} n_{ij} &- \text{number of samples in category} \; (i,j) \\ n_{i \bullet} &= \sum_{j=1}^{b} n_{ij} \\ n_{\bullet j} &= \sum_{i=1}^{a} n_{ij} \\ n &= \sum_{i=1}^{a} \sum_{j=1}^{b} n_{ij} \; . \end{split}$

Proof: In two-way ANOVA, model parameters are subject to the constraints

$\label{eq:anova2-cons} \begin{split} \sum_{i=1}^{a} w_{ij} \alpha_i &= 0 \quad \text{for all} \quad j = 1, \ldots, b \\ \sum_{j=1}^{b} w_{ij} \beta_j &= 0 \quad \text{for all} \quad i = 1, \ldots, a \\ \sum_{i=1}^{a} w_{ij} \gamma_{ij} &= 0 \quad \text{for all} \quad j = 1, \ldots, b \\ \sum_{j=1}^{b} w_{ij} \gamma_{ij} &= 0 \quad \text{for all} \quad i = 1, \ldots, a \end{split}$

where $w_{ij} = n_{ij}/n$. The residual sum of squares for this model is

$\label{eq:rss} \mathrm{RSS}(\mu,\alpha,\beta,\gamma) = \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} \varepsilon_{ijk}^2 = \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} (y_{ij} - \mu - \alpha_i - \beta_j - \gamma_{ij})^2$

and the derivatives of $\mathrm{RSS}$ with respect to $\mu$, $\alpha$, $\beta$ and $\gamma$ are

$\label{eq:rss-der-mu} \begin{split} \frac{\mathrm{d}\mathrm{RSS}}{\mathrm{d}\mu} &= \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} \frac{\mathrm{d}}{\mathrm{d}\mu} (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij})^2 \\ &= \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} -2 (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij}) \\ &= \sum_{i=1}^{a} \sum_{j=1}^{b} \left( 2 n_{ij} \mu + 2 n_{ij} (\alpha_i + \beta_j + \gamma_{ij}) - 2 \sum_{k=1}^{n_{ij}} y_{ijk} \right) \\ &= 2 n \mu + 2 \left( \sum_{i=1}^{a} n_{i \bullet} \alpha_i + \sum_{j=1}^{b} n_{\bullet j} \beta_j + \sum_{i=1}^{a} \sum_{j=1}^{b} n_{ij} \gamma_{ij} \right) - 2 \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \end{split}$ $\label{eq:rss-der-alpha} \begin{split} \frac{\mathrm{d}\mathrm{RSS}}{\mathrm{d}\alpha_i} &= \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} \frac{\mathrm{d}}{\mathrm{d}\alpha_i} (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij})^2 \\ &= \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} -2 (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij}) \\ &= 2 n_{i \bullet} \mu + 2 n_{i \bullet} \alpha_i + 2 \left( \sum_{j=1}^{b} n_{ij} \beta_j + \sum_{j=1}^{b} n_{ij} \gamma_{ij} \right) - 2 \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \end{split}$ $\label{eq:rss-der-beta} \begin{split} \frac{\mathrm{d}\mathrm{RSS}}{\mathrm{d}\beta_j} &= \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} \frac{\mathrm{d}}{\mathrm{d}\beta_j} (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij})^2 \\ &= \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} -2 (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij}) \\ &= 2 n_{\bullet j} \mu + 2 n_{\bullet j} \beta_j + 2 \left( \sum_{i=1}^{a} n_{ij} \alpha_i + \sum_{i=1}^{a} n_{ij} \gamma_{ij} \right) - 2 \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} \end{split}$ $\label{eq:rss-der-gamma} \begin{split} \frac{\mathrm{d}\mathrm{RSS}}{\mathrm{d}\gamma_{ij}} &= \sum_{k=1}^{n_{ij}} \frac{\mathrm{d}}{\mathrm{d}\gamma_{ij}} (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij})^2 \\ &= \sum_{k=1}^{n_{ij}} -2 (y_{ijk} - \mu - \alpha_i - \beta_j - \gamma_{ij}) \\ &= 2 n_{ij} (\mu + \alpha_i + \beta_j + \gamma_{ij}) - 2 \sum_{k=1}^{n_{ij}} y_{ijk} \; . \end{split}$

Setting these derivatives to zero, we obtain the estimates of $\mu_i$, $\alpha_i$, $\beta_j$ and $\gamma_{ij}$:

$\label{eq:rss-der-mu-zero} \begin{split} 0 &= 2 n \hat{\mu} + 2 \left( \sum_{i=1}^{a} n_{i \bullet} \alpha_i + \sum_{j=1}^{b} n_{\bullet j} \beta_j + \sum_{i=1}^{a} \sum_{j=1}^{b} n_{ij} \gamma_{ij} \right) - 2 \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \hat{\mu} &= \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \sum_{i=1}^{a} \frac{n_{i \bullet}}{n} \alpha_i - \sum_{j=1}^{b} \frac{n_{\bullet j}}{n} \beta_j - \sum_{i=1}^{a} \sum_{j=1}^{b} \frac{n_{ij}}{n} \gamma_{ij} \\ &\overset{\eqref{eq:samp-size}}{=} \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \sum_{j=1}^{b} \sum_{i=1}^{a} \frac{n_{ij}}{n} \alpha_i - \sum_{i=1}^{a} \sum_{j=1}^{b} \frac{n_{ij}}{n} \beta_j - \sum_{i=1}^{a} \sum_{j=1}^{b} \frac{n_{ij}}{n} \gamma_{ij} \\ &\overset{\eqref{eq:anova2-cons}}{=} \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ &\overset{\eqref{eq:mean-samp}}{=} \bar{y}_{\bullet \bullet \bullet} \end{split}$ $\label{eq:rss-der-alpha-zero} \begin{split} 0 &= 2 n_{i \bullet} \hat{\mu} + 2 n_{i \bullet} \hat{\alpha}_i + 2 \left( \sum_{j=1}^{b} n_{ij} \beta_j + \sum_{j=1}^{b} n_{ij} \gamma_{ij} \right) - 2 \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \hat{\alpha}_i &= \frac{1}{n_{i \bullet}} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \hat{\mu} - \sum_{j=1}^{b} \frac{n_{ij}}{n_{i \bullet}} \beta_j - \sum_{j=1}^{b} \frac{n_{ij}}{n_{i \bullet}} \gamma_{ij} \\ &= \frac{1}{n_{i \bullet}} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \hat{\mu} - \frac{n}{n_{i \bullet}} \sum_{j=1}^{b} \frac{n_{ij}}{n} \beta_j - \frac{n}{n_{i \bullet}} \sum_{j=1}^{b} \frac{n_{ij}}{n} \gamma_{ij} \\ &\overset{\eqref{eq:anova2-cons}}{=} \frac{1}{n_{i \bullet}} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ &\overset{\eqref{eq:mean-samp}}{=} \bar{y}_{i \bullet \bullet} - \bar{y}_{\bullet \bullet \bullet} \end{split}$ $\label{eq:rss-der-beta-zero} \begin{split} 0 &= 2 n_{\bullet j} \hat{\mu} + 2 n_{\bullet j} \hat{\beta}_j + 2 \left( \sum_{i=1}^{a} n_{ij} \alpha_i + \sum_{i=1}^{a} n_{ij} \gamma_{ij} \right) - 2 \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} \\ \hat{\beta}_j &= \frac{1}{n_{\bullet j}} \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} - \hat{\mu} - \sum_{i=1}^{a} \frac{n_{ij}}{n_{\bullet j}} \alpha_i - \sum_{i=1}^{a} \frac{n_{ij}}{n_{\bullet j}} \gamma_{ij} \\ &= \frac{1}{n_{\bullet j}} \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} - \hat{\mu} - \frac{n}{n_{\bullet j}} \sum_{i=1}^{a} \frac{n_{ij}}{n} \alpha_i - \frac{n}{n_{\bullet j}} \sum_{i=1}^{a} \frac{n_{ij}}{n} \gamma_{ij} \\ &\overset{\eqref{eq:anova2-cons}}{=} \frac{1}{n_{\bullet j}} \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} - \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ &\overset{\eqref{eq:mean-samp}}{=} \bar{y}_{\bullet j \bullet} - \bar{y}_{\bullet \bullet \bullet} \end{split}$ $\label{eq:rss-der-gamma-zero} \begin{split} 0 &= 2 n_{ij} (\hat{\mu} + \hat{\alpha}_i + \hat{\beta}_j + \hat{\gamma_{ij}}) - 2 \sum_{k=1}^{n_{ij}} y_{ijk} \\ \hat{\gamma_{ij}} &= \frac{1}{n_{ij}} \sum_{k=1}^{n_{ij}} y_{ijk} - \hat{\alpha}_i - \hat{\beta}_j - \hat{\mu} \\ &= \frac{1}{n_{ij}} \sum_{k=1}^{n_{ij}} y_{ijk} - \frac{1}{n_{i \bullet}} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} - \frac{1}{n_{\bullet j}} \sum_{i=1}^{a} \sum_{k=1}^{n_{ij}} y_{ijk} + \frac{1}{n} \sum_{i=1}^{a} \sum_{j=1}^{b} \sum_{k=1}^{n_{ij}} y_{ijk} \\ &\overset{\eqref{eq:mean-samp}}{=} \bar{y}_{i j \bullet} - \bar{y}_{i \bullet \bullet} - \bar{y}_{\bullet j \bullet} + \bar{y}_{\bullet \bullet \bullet} \; . \end{split}$
Sources:

Metadata: ID: P371 | shortcut: anova2-ols | author: JoramSoch | date: 2022-11-06, 15:55.